Reframing the Alhambra : Architecture, poetry, textiles and court ceremonial - Bush, Olga (Edinburgh studies in Islamic art., 2018)
The Nasrid builders of the Alhambra - the best-preserved medieval Muslim palatial city - were so exacting that some of their work could not be fully explained until the invention of fractal geometry. Their design principles have been obscured, however, by the loss of all archival material. This book resolves that impasse by investigating the neglected, interdisciplinary contexts of medieval poetics and optics and through comparative study of Islamic court ceremonials. This reframing enables the reconstruction of the underlying, integrated aesthetic, focusing on the harmonious interrelationship between diverse artistic media - architecture, poetry and textiles - in the experience of the beholder, resulting in a new understanding of the Alhambra.